Optical Manipulation of Gb3 Enriched Lipid Domains: Impact of Isomerization on Gb3‐Shiga Toxin B Interaction. Issue 4 (28th November 2022) - Socrier, Larissa; Ahadi, Somayeh; Bosse, Mathias; Montag, Cindy; Werz, Daniel B.; Steinem, Claudia
Abstract: The plasma membrane is a complex assembly of proteins and lipids that can self‐assemble in submicroscopic domains commonly termed "lipid rafts", which are implicated in membrane signaling and trafficking. Recently, photo‐sensitive lipids were introduced to study membrane domain organization, and photo‐isomerization was shown to trigger the mixing and de‐mixing of liquid‐ordered ( l o ) domains in artificial phase‐separated membranes. Here, we synthesized globotriaosylceramide (Gb3 ) glycosphingolipids that harbor an azobenzene moiety at different positions of the fatty acid to investigate light‐induced membrane domain reorganization, and that serve as specific receptors for the protein Shiga toxin (STx). Using phase‐separated supported lipid bilayers on mica surfaces doped with four different photo‐Gb3 molecules, we found by fluorescence microscopy and atomic force microscopy that liquid disordered ( l d ) domains were formed within l o domains upon trans ‐ cis photo‐isomerization. The fraction and size of these l d domains were largest for Gb3 molecules with the azobenzene group at the end of the fatty acid. We further investigated the impact of domain reorganization on the interaction of the B‐subunits of STx with the photo‐Gb3 . Fluorescence and atomic force micrographs clearly demonstrated that STxB binds to the l o phase if Gb3 is in the trans ‐configuration, whereas two STxB populations are formed if the photo‐Gb3 is switched to the cis ‐configuration highlighting the idea of manipulating lipid‐protein interactions with a light stimulus. Abstract : Switch it on : Gb3 sphingolipids with azobenzene groups serve as light‐triggered nano‐tools to control lipid and protein domains. By using the ability of Gb3 to bind Shiga toxin, its photo‐isomerization alters the protein distribution on liquid‐ordered domains and induces submicrometer‐sized protein lakes. This may offer new strategies for controlling the structure of biological membranes including membrane‐interacting proteins.